2018
DOI: 10.1364/oe.26.005292
|View full text |Cite
|
Sign up to set email alerts
|

Refractive-index-modified-dot Fabry-Perot fiber probe fabricated by femtosecond laser for high-temperature sensing

Abstract: An optical fiber Fabry-Perot probe sensor for high-temperature measurement is proposed and demonstrated, which is fabricated by inducing a refractive-index-modified-dot (RIMD) in the fiber core near the end of a standard single mode fiber (SMF) using a femtosecond laser. The RIMD and the SMF end faces form a Fabry-Perot interferometer (FPI) with a high-quality interference fringe visibility (>20dB). As a high-temperature sensor, such an FPI exhibits a sensitivity of 13.9pm/°C and 18.6pm/°C in the range of 100-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…It has a more compact structure for developing high-performance temperature microprobes. Femtosecond laser [31] or ion beam etching technology [32], as well as high-precision fiber-splicing technology [36,37], can improve its temperature detection limit to as high as 1200 °C, making it suitable for extreme high temperature environments; furthermore, sol coating [35] or temperature-sensitive polymer encapsulation technology [39] can be used for enhance normal temperature microprobes, which will be a promising candidate for implantable microsensors for health or environmental monitoring under 200 °C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a more compact structure for developing high-performance temperature microprobes. Femtosecond laser [31] or ion beam etching technology [32], as well as high-precision fiber-splicing technology [36,37], can improve its temperature detection limit to as high as 1200 °C, making it suitable for extreme high temperature environments; furthermore, sol coating [35] or temperature-sensitive polymer encapsulation technology [39] can be used for enhance normal temperature microprobes, which will be a promising candidate for implantable microsensors for health or environmental monitoring under 200 °C.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above complex optical fiber structures, single polymer optical fibers have been demonstrated with a temperature sensitivity of ~10 −3 °C [27], where the temperature performance were revealed by the transmission power and the effect of relative and twist have been experimentally obtained [28,29]. Furthermore, their packaging size is hard to reduce further depending on the bending loss of the optical fiber [30], which will seriously limit their application in a narrow space; the latter ones are carried out as reflective structures, where the temperature sensitive cavity was constructed at the end of the optical fiber by laser or ion beam processing, chemical etching or film forming and special fiber splicing technologies [31,32,33,34,35,36,37]. Among them, femtosecond laser processing can machine a refractive index turning point with good repeatability in the optical fiber, which was used as a Fabry-Perot cavity and can work at high temperatures up to 1000 °C [31]; focused ion beams can etch an air cavity at the tip of an optical fiber, based which a Fabry-Perot temperature sensor with a sensitivity of −654 pm/°C has been experimentally demonstrated [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fiber temperature sensor has progressed considerably in recent years due to its advantages of small size, light weight, high sensitivity, corrosion resistance, and intrinsic safety [3]- [7]. The current fiber temperature sensors are divided into fiber Bragg grating (FBG) [8], [9] and Mach-Zehnder interferometric (MZI) [10], [11], Fabry-Perot interferometric (FPI) [12], [13], distributed [14], according to the structure type, and is divided into side-polished [15], [16], and coating [17], according to the processing technology. The classical FBG utilizes the difference in thermal expansion coefficients between the fiber core and cladding temperature sensing, but its sensor has low temperature sensitivity due to minimal differences.…”
Section: Introductionmentioning
confidence: 99%
“…The reflective FPI temperature sensor could operate in harsh and narrow environment with high flexibility; however, it always had low sensitivity. For example, Wei Peng et al [22] reported an FPI based on the twin-core photonic crystal fiber to test the temperature. A single-mode fiber was welded to a 164 μm twin-core photonic crystal fiber, wherein the welding face of both fibers was the first reflector, the end-face of the twin-core photonic crystal fiber was the second reflector, and the two reflectors formed an FP cavity.…”
Section: Introductionmentioning
confidence: 99%